White blood cell traits and lung cancer risk: a two-sample mendelian randomization analysis - Kaijun Long; Zhengfeng Zhu; Xinzhe Zheng; Gang Xu; Cheng Chen; Xixian Ke (Scientific Reports, 2025)
Abstract This study aimed to investigate the potential association between white blood cell counts and the risk of lung cancer, including its subtypes, through Mendelian randomization (MR) analysis. We conducted a two-sample MR analysis using genome-wide association study (GWAS) summary statistics for the both exposure traits (eosinophil count, neutrophil count, lymphocyte count, monocyte count, basophil count, and total white blood cell count) and outcome traits (lung cancer and its subtypes). The GWAS dataset for lung cancer included 29,266 cases (11273 lung adenocarcinoma (LUAD), 7426 lung squamous cell carcinoma (LSCC), 2664 small cell lung cancer (SCLC)) and 56,450 controls. In MR analysis, we employed methods such as Inverse variance weighted (IVW), weighted median, MR-Egger regression, MR pleiotropy residual sum and outlier. MR analysis revealed an elevated total white blood cell (WBC) count significantly increased the risk of LUAD (IVW: OR = 1.484, 95% CI = 1.219–1.749, p = 0.003). The results confirmed a causal relationship between monocyte count and LUAD (IVW: OR = 1.687, 95% CI:1.542–1.830, p < 0.001). An increased total WBC count was associated with a higher risk of LUAD. Additionally, analysis of WBC subtypes counts indicated that monocyte count plays an crucial role in the elevated risk of LUAD.